FABRICATION OF A NOVEL HIGH-DENSITY THREE-DIMENSIONAL (3D)-PRINTED DEVICE FOR DOMPERIDONE TABLETS - Charoenying, Thapakorn; Chaksmithanont, Prin; Panomsuk, Suwannee; Nattapulwat, Nattawat; Plianwong, Samarwadee; Patrojanasophon, Prasopchai; Opanasopit, Praneet (ไทยไภษัชยนิพนธ์, 2023)
In conventional high-density tablets, a large amount of high-density material must be directly added to the tablets. Therefore, it may lead to undesired tablet properties. The aim of this study was to develop novel high-density three-dimensional (3D)-printed devices (HPDs) for a gastro-retentive drug delivery system (GRDDS). The HPDs were fabricated from iron powder-loaded polylactic acid (PLA) filaments using fused deposition modeling (FDM). A commercial domperidone (DOM) tablet was utilized as a model drug and placed into HPDs. To enable different drug release characteristics, the devices were fabricated with different hole diameters (1.0, 1.5, and 2.0 mm). The appearance, weight variation, and density of the HPDs were evaluated. In vitro dissolution of DOM from the HPDs was conducted to obtain the drug release characteristics. The kinetics of DOM release from HPDs was examined to elucidate the release mechanism. The printed HPDs had similar physical appearances to the designed 3D models. The HPDs had a density of more than or equal to 2.4 g/cm3 with a slightly rough texture due to the original texture of iron powder-loaded polylactic acid (PLA) filaments. The HPD with hole diameters of 1.5 mm showed an optimal sustained-release profile, with 98.8% of the drug released in 12 h because of the limit of the tablet’s surface area exposed to the medium. Moreover, zero-order kinetics was achieved from all HPDs. It can be concluded that HPDs successfully modified the drug release of regular DOM tablets to GRDDS without adding high-density excipients into the tablet directly and may be applied to other commercial drugs as a high-density drug delivery system.